Exploring Students’ Perspective on Using Online Collaborative Platform in Biology Laboratory Work - Rizqa Devi Anazifa; Suratsih Suratsih; Paramita Cahyaningrum Kuswandi; Anggi Tias Pratama (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2023)
The COVID-19 pandemic has changed the teaching and learning methods. Learning activities that were originally done face-to-face must be adjusted to online learning. This change also occurs in laboratory activities. As students must adapt to the different method of learning, their behavior in learning is affected, as well, including how they collaborate in laboratory work that is conducted online. This study aims to explore students’ perspective on online collaborative learning tool in biology laboratory work. The online collaborative learning process is supported by a collaboration platform called Trello. Survey was conducted by collecting responses from students in Department of Biology Education who participated in the genetics laboratory work. This study was conducted using survey, which was conducted after students had participated in laboratory work for two weeks online using the virtual collaborative platform. The questionnaires measured students’ perspectives on using Trello for collaborating with their team during laboratory work. The instrument also measured students’ perception on how Trello supported their collaborative learning online including effective group teamwork, discussion activities, and communication within group such as asking questions, answering questions, and making arguments. A number of 127 valid responses were analyzed descriptively. The result showed that students agreed that Trello was easy to use (97%) and supported them to conduct group work easily (98%) and discussion more effectively (87%). Result from this study provides positive evidence on how Trello supports students’ collaboration during laboratory work.